An investigation of the conceptualization of peace and war in peace journalism studies of media coverage of national and international conflicts. (December 2019) - Gouse, Valerie; Valentin-Llopis, Mariely; Perry, Stephen; Nyamwange, Beryl
According to Galtung's articles 'On the role of the media in worldwide security and peace' (1986) and 'High road, low road: Charting the course for peace journalism' (1998), war journalism and peace journalism are two competing frames when reporting news on war and conflict. War journalists reactively report on conflict in a way that propagates violence, victory, and an elitist orientation. On the contrary, peace journalists proactively report on the causes of and solutions to a conflict, giving voice to all parties through responsible, empathetic journalism. By searching databases for multiple examples of qualitative and quantitative literature on peace and war journalism, new paths to best practices of how scholars articulate and measure the concepts of peace and war using content analysis methods can be found. This article reports on studies published in peer-reviewed journals that investigate the attributes of peace and war as they are conceptualized by scholars analyzing newspaper articles, television broadcasts, and radio reports within the context of peace journalism. Results suggest the majority of peace journalism studies examine media surrounding direct violence as it is occurring, and assess it most often by using the war/peace indicator of elite-oriented versus people-oriented.